Implementasi Pengembangan Ekowisata Berbasis Partisipasi Masyarakat (Studi Kasus: Program Langgeng Ecotourism Desa Nyambu Kabupaten Tabanan - Rahmayanti, Dwi Sukma; Supriliyani, Ni Wayan; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2019)
ABSTRACT Ecotourism development is part of a sustainable tourism policy. Ecotourism aims to support environmental preservation of nature and culture, also increase community participation to provide economic benefits to the community and local government. One of the villages that began to developing ecotourism is Nyambu Village in Tabanan Regency. Ecotourism development through the Langgeng Ecotourism program begins with the excavation of village potential in the form of natural and cultural resources. The purpose of this study is to find out and understand the implementation of community-based ecotourism development (case study: langgeng ecotourism program in Nyambu Village, Tabanan Regency). The method used in the research is qualitative with descriptive analysis. The results of the research show that implementation of Nyambu Village ecotourism development has been going well but problems still arise in the community’s concern to protect the environment, especially in the management of plastic waste. Keyword: development of ecotourism, langgeng ecotourism program, community participation